1996
DOI: 10.1136/adc.75.6.494
|View full text |Cite
|
Sign up to set email alerts
|

Epogam evening primrose oil treatment in atopic dermatitis and asthma.

Abstract: Essential fatty acids are claimed to have positive effects in atopic diseases. In a double blind, placebo controlled, parallel group study 58 out of 60 children, with atopic dermatitis and the need for regular treatment with topical skin steroids, completed a 16 weeks' treatment period with either Epogam evening primrose oil or placebo capsules. Twenty two ofthese subjects also had asthma. The parents used diaries to record symptom scores and concomitant medication. Peak expiratory flow was measured and diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…Blinding was adequately described in 22 studies (85%; Figure 2); one of these used an emetic (Ipecacuanha) to mask the side effect of the intervention (Tylophora). 22 Only seven studies (27%) reported withdrawals 13,19,23,24,28,34,35 and only one study gave adequate descriptions of all three domains.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Blinding was adequately described in 22 studies (85%; Figure 2); one of these used an emetic (Ipecacuanha) to mask the side effect of the intervention (Tylophora). 22 Only seven studies (27%) reported withdrawals 13,19,23,24,28,34,35 and only one study gave adequate descriptions of all three domains.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40] All were double blinded except one single blinded study where the colours of study and placebo medicine sachets differed. 26 Sample sizes ranged from eight 32 to 334, 13 six studies recruited children 13,14,19,23,24,35 although one of these reported subjects up to age 55 24 (clarification was sought but not received) -and one a mixed age group of 14-20 yrs. 21 Age was not stated in five studies, 17,25,27,37,38 and the remainder recruited adults.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations